GOOGLE ADSENSE PERSPEKTIF HUKUM PERJANJIAN ISLAM - Muhammad Bahaur Rijal; Nahara Eriyanti (Universitas Islam Negeri Ar-Raniry, 2019)
This research examines is about the mechanism of the Google Adsense contract viewed from the legal aspects of the Islamic agreement. Google Adsense mechanism is different from business mechanisms in general, the differentiation is seen from the involvement of advertisers, Google and publishers who are bound in an online contract system. The purpose of this research is to find out how the mechanism of Google Adsense, besides analyzing the legal theory of Islamic agreements on the mechanism of Google Adsense. Type of research is a descriptive-analytical field research using a pattern of Islamic legal approach. There are two theories on which this research is based, namely contract theory and online business theory for analyzing legal aspects. The contract theory used focuses on the theory of the muamalat legal perspective contract which is then used to analyze transactions in Google Adsense, then from that analysis will be known how the law of the Google Adsense business. The results of this study indicate that the mechanism that occurs in Google Adsense reflects the basic values of the contract that are in accordance with the rules of the contract law. Standard contract enforcement aims to avoid moral hazard to protect the parties involved in online business for the realization of mutual benefit and prosperity. In addition, the screening efforts imposed on Google Adsense aim to demonstrate the application of business ethics values, which are known to have implications for the validity of the contract (in accordance with Islamic treaty law)